PENGARUH UKURAN PERUSAHAAN, FASILITAS PERPAJAKAN, TINGKAT UTANG DAN INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK - Syavira, Intan; Indradi, Donny (Publika Citra Media, 2025)
This study aims to analyze the effect of company size, tax facilities, debt level, and inventory intensity on tax management. The research was conducted by analyzing the financial statements of companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The sample used in this study consists of 22 companies from the Consumer Non-Cyclicals sector listed on the IDX during the period from 2019 to 2022, selected using purposive sampling technique. The data used in this study is secondary data in the form of financial reports from each company included in the research sample. The variables used in this study are Company Size, Tax Facilities, Debt Level, and Inventory Intensit as Independent Variables, and Tax Management as the Dependent Variable. Panel data regression method is used as the research methodology. The analysis of the research results was conducted with the assistance of EViews 12 Student Version Lite software. The research results show that the best model is the Fixed Effect Model (FEM). The findings indicate that Company Size has an effect on Tax Management, Tax Facilities do not affect Tax Management, Debt Level does not affect Tax Management, Inventory Intensity does not affect Tax Management, and Company Size, Tax Facilities, Debt Level, and Inventory Intensity collectively affect Tax Management.